Occupational ergonomics : work related musculoskeletal disorders of the upper limb and back - Violante, Francesco; Kilbom, Åsa; Armstrong, Thomas J. (Taylor & Francis, 2000)
A collection of lectures from renowned international experts from the 1999 International Course for the Advanced Training in Occupational Health. Deals with work-related musculoskeletal disorders.
Keywords: Musculoskeletal system -- Diseases.; Musculoskeletal system -- Wounds and injuries.; Industrial accidents.; Human engineering.; Occupational diseases.; Arm -- Wounds and injuries.; Back -- Wounds and injuries.; Neck Injuries; Occupational Health; Ergonomics; Occupational Diseases; Arm Injuries; Back Injuries; Occupational Diseases -- prevention & control; Musculoskeletal Diseases; Back Injuries -- prevention & control; Arm Injuries -- prevention & control; Neck Injuries -- prevention & control; Appareil locomoteur -- Maladies.; Appareil locomoteur -- Lésions et blessures.; Ergonomie.; Maladies professionnelles.; Bras -- Lésions et blessures.; Dos -- Lésions et blessures.; ergonomics.; MEDICAL -- Orthopedics.; HEALTH & FITNESS -- Diseases -- Musculoskeletal.; MEDICAL -- Rheumatology.; Occupational diseases; Arm -- Wounds and injuries; Human engineering; Industrial accidents; Musculoskeletal system -- Diseases; Musculoskeletal system -- Wounds and injuries; Electronic books.; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.